Learning Anxiety and Parenting Pattern on Learning Achievement - Fitriyani Hali; Saswina Saswina; Gemi Susanti (Sultra Educational Journal, 2021)
The purpose of this study was to determine the effect of learning anxiety and parenting patterns on student achievement. This research is an ex post facto research conducted at SMP Negeri 3 Kolaka in class VIII. The population referred to in this study is the entire class VIII with a total of 68 students. The sample used in the study is a saturated sample. This research data was collected using a questionnaire technique to investigate learning anxiety and parenting patterns and using documentation to collect data on mathematics learning achievement taken from the grade VIII student report cards of SMP Negeri 3 Kolaka in the even semester. The conclusion obtained is that there is an effect of learning anxiety and parenting patterns simultaneously on the mathematics learning achievement of eighth grade students of SMP Negeri 3 with the contribution level of learning anxiety and parenting patterns on students' mathematics learning achievement of 1.61%.